2-Methoxy-7-Acetonyljuglone Isolated from Reynoutria japonica Increases the Activity of Nuclear Factor Erythroid 2-Related Factor-2 through Inhibition of Ubiquitin Degradation in HeLa Cells - Jung-Hwan Kim; Atif Ali Khan Khalil; Hye-Jin Kim; Sung-Eun Kim; Mi-Jeong Ahn (MDPI AG, 2019)
The nuclear factor erythroid-derived 2-related factor 2 (NRF2) is a key transcription factor for the activation of genes responsible for oxidative stress and drug detoxification. Thus, it is important to identify NRF2 activators, which can be used to protect the cells from oxidative damage. Here, we investigated the effect of juglone derivatives isolated from Reynoutria japonica on the activity of NRF2 in HeLa cells. We demonstrated that among the juglone derivatives, 2-methoxy-7-acetonyljuglone (MA) strongly stimulated the antioxidant response element (ARE)-luciferase activity in a dose-dependent manner. In addition, MA significantly increased the nuclear localization of NRF2 and, consequently, increased the expression of NRF2 target genes, including heme oxygenase-1(HO-1), NAD(P)H: quinine oxidoreductase-1 (NQO-1), and glutamate-cysteine ligase catalytic (GCLC). To gain insights into the NRF2 signaling mechanism by MA, we measured the activities of RAC-alpha serine/threonine-protein kinase (AKT) and mitogen-activated protein (MAP) kinase family proteins, including extracellular signal-regulated kinase (ERK) and p38. Our results showed that MA induced NRF2 activity through p38 and AKT signaling. Subsequently, we found that MA significantly enhanced NRF2 stability by inhibiting ubiquitin-dependent proteasomal degradation. Thus, MA might protect cells by enhancing the activity and stability of NRF2 through inhibition of the proteasomal degradation pathway.